ZAREBA, Slawomir H.; ZARZECKI, Marcin (Ed.). Between construction and deconstruction of the universes of meaning: research into the religiosity of academic youth in the years 1988-1998-2005-2017 - Coutinho, José Pereira (REVER: Revista de Estudos da Religião, 2021)
Resenha